Effects of binders and internal lubricant compositions on mechanical properties of dry pressed sintered alumina - Ismail Zainol (Tanjong Malim, 2019)
Effects of binders and internal lubricant compositions on mechanical properties of dry pressed sintered alumina by Ismail Zainol